An examination of the mediating effect of islamic work ethic on the relationships between transformational leadership and work outcomes - Rokhman, Wahibur; Rivai , Harif Amali; Adewale, Abideen Adeyemi (Universitas Gadjah Mada, 2011)
This study investigates the role of Islamic work ethic as mediator between transformational leadership and work outcomes (organizational commitment, job satisfaction and turnover intention). This study used a sample of 370 employees from 60 Islamic microfinance institutions in Central Java, Indonesia. The results of Structural Equation Modeling (SEM) indicate that transformational leadership has a positively significant impact on Islamic work ethic. The findings also noted that Islamic work ethic directly and positively affect both organizational commitment and job satisfaction on the one hand, and negatively influences turnover intention on the other. Overall the model supported that Islamic work ethic has a significant role to mediate the the relationship betweem transformational leadership and work outcomes. Implication, limitation and suggestion for future research are discussed.